1997
DOI: 10.1002/(sici)1097-4547(19970515)48:4<287::aid-jnr1>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cytokine transcripts in the central nervous system and pituitary following peripheral administration of endotoxin to mice

Abstract: The regional distribution and inducibility of cytokines in the normal brain is still a matter of controversy. As an attempt to clarify this issue, we studied the constitutive and induced expression of interleukin (IL)-1beta, IL-6, tumor necrosis factor (TNF)-alpha, and interferon (IFN)-gamma mRNAs in the brain, pituitary, and spleen of mice using qualitative and semiquantitative reverse-transcription polymerase chain reaction. The contribution of nonbrain cells to the cytokine transcripts detected was consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
114
1
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 182 publications
(127 citation statements)
references
References 37 publications
7
114
1
1
Order By: Relevance
“…To determine the contribution of contaminating blood cells to the signals obtained in the experimental brain samples, serial 1:10 dilutions of cDNAs from peripheral blood of the corresponding experimental animals were amplified. The last dilution tested contained cDNA derived from 3 ng of total RNA and represents 10 times any possible contribution of blood cells to the cytokine signal (Pitossi et al, 1997). This last dilution showed no detectable blood-borne signal for all cytokines tested (data not shown).…”
Section: Local Inflammation Produced By Turpentine Does Not Elicit Mementioning
confidence: 95%
See 1 more Smart Citation
“…To determine the contribution of contaminating blood cells to the signals obtained in the experimental brain samples, serial 1:10 dilutions of cDNAs from peripheral blood of the corresponding experimental animals were amplified. The last dilution tested contained cDNA derived from 3 ng of total RNA and represents 10 times any possible contribution of blood cells to the cytokine signal (Pitossi et al, 1997). This last dilution showed no detectable blood-borne signal for all cytokines tested (data not shown).…”
Section: Local Inflammation Produced By Turpentine Does Not Elicit Mementioning
confidence: 95%
“…IL-1␤, IL-6, and TNF-␣ cDNAs were quantified from 200 ng of reverse-transcribed RNA by co-amplification with 100 fg of a multispecific internal control (pRat6) by PCR, as described previously (Bouaboula et al, 1992;Pitossi et al, 1997). pRat6 carries priming sites for several rat cytokines and house-keeping genes, including IL-1␤, IL-6, TNF-␣, and ␤-microglobulin (Pitossi and Besedovsky, 1996).…”
Section: Semi-quantitative Rt-pcr (Sq-pcr)mentioning
confidence: 99%
“…It is known that peripheral inflammation can stimulate central inflammatory cytokine mRNA and protein synthesis (Laye et al, 1994;Pitossi et al, 1997) and that these cytokines coordinate a group of adaptive behavioral changes collectively known as sickness behavior (Konsman et al, 2002). In prion-diseased mice, in which there is prior microglial activation, LPS induces exaggerated sickness behavior and increased central synthesis of IL-1␤ (Combrinck et al, 2002).…”
Section: Cns Consequences Of Systemic Inflammationmentioning
confidence: 99%
“…However, it is also known that peripheral infection can initiate the synthesis of cytokines within the CNS (Laye et al, 1994;Pitossi et al, 1997). We have shown recently that systemic challenge with bacterial endotoxin [lipopolysaccharide (LPS)] provokes exaggerated CNS IL-1␤ synthesis and sickness behavior responses in animals with ongoing chronic inflammation (Combrinck et al, 2002), and this also appears to be true in transgenic models of AD (Sly et al, 2001;Lee et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The stimulation of TLRs by their respective ligands triggers the expression of several genes that are involved in the synthesis of chemokines and cytokines, as well as adhesive and co-stimulatory molecules (Takeda et al, 2003). It has been demonstrated that peripheral inflammation can stimulate the synthesis of inflammatory cytokines in the brain (Laye et al, 1994;Pitossi et al, 1997). In general, the brain is protected from pathogens through brain barriers.…”
mentioning
confidence: 99%